Gene expression profiling toward the next generation safety control of influenza vaccines and adjuvants in Japan. Issue 43 (15th October 2018) - Momose, Haruka; Sasaki, Eita; Kuramitsu, Madoka; Hamaguchi, Isao; Mizukami, Takuo
Abstract: Influenza becomes epidemic worldwide every year, and many individuals receive vaccination annually. Quality control relating to safety and potency of influenza vaccines is important to maintain public confidence. The safety of influenza vaccines has been assessed by clinical trials, and animal safety tests are performed to monitor the consistent quality between vaccines used for clinical trials and marketing; the biological responses in vaccinated animals are evaluated, including changes in body weight and white blood cell count. Animal safety tests have been contributing to the quality relating to the safety of influenza vaccines for decades, but improvements are needed. Although precise mechanisms involving biological changes in animal safety tests have not been fully elucidated, the application of cDNA microarray technology make it possible to reliably identify genes related to biological responses in vaccinated animals. From analysis of the expression profile of >10, 000 genes of lung in animals treated with an inactivated whole virion influenza vaccine, we identified 17 marker genes whose expression patterns correlated well to changes in body weight and leukocyte count in vaccinated animals. In influenza HA vaccine-treated animals exhibiting subtle changes in biological responses, a robust expression pattern of marker genes was found. Furthermore, these marker genes could also be used in the evaluation of adjuvanted influenza vaccines. The expression profile of marker genes is expected to be an alternative indicator for safety control of various influenza vaccines conferring high sensitivity and short turnaround time. Thus, gene expression profiling may be a powerful tool for safety control of vaccines in the future.